2019
DOI: 10.31351/vol28iss2pp9-16
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effects of Arabic gum (Acacia): A mini review

Abstract: Gum Arabic is a natural gummy exudate gained from the trees of Acacia species (Acacia senegal and Acacia seyal), Family: Fabaceae. Gum Arabic considers as a dietary fiber with a high percentage of carbohydrates and low protein content. Sugars arabinose and ribose were originally discovered and isolated from gum Arabic and it is representing the original source of these sugars. A gum emanation from trees occurs under stress conditions such as heat, poor soil fertility, drought, and injury. Mainly gum is produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…In this assay, the percentage inhibition of curcumin and Cur/GANPs was proportional to the decrease of absorbance measurements at 228 nm. Cur/GANPs had more potent ACE inhibitory effects compared to free curcumin, which may be attributed to the increase in bioavailability of curcumin and the synergistic properties of gum Arabic coating (Hassani et al, 2019;Jaafar, 2019). Therefore, it can be suggested that encapsulation of curcumin in gum Arabic could improve the antihypertensive capacity of curcumin and such a complexation of gum Arabic with curcumin may represent an important alternative antihypertensive treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In this assay, the percentage inhibition of curcumin and Cur/GANPs was proportional to the decrease of absorbance measurements at 228 nm. Cur/GANPs had more potent ACE inhibitory effects compared to free curcumin, which may be attributed to the increase in bioavailability of curcumin and the synergistic properties of gum Arabic coating (Hassani et al, 2019;Jaafar, 2019). Therefore, it can be suggested that encapsulation of curcumin in gum Arabic could improve the antihypertensive capacity of curcumin and such a complexation of gum Arabic with curcumin may represent an important alternative antihypertensive treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It is a widely known safe dietary fiber and affects bacterial mass and enzyme activity; the bacteria count of the cecum may increase due to a higher dietary fiber content without altering the bacteria types present. The relative quantities of acetate and butyrate produced depend on the amount of AG fed [11].…”
Section: Introductionmentioning
confidence: 99%
“…It is one of the oldest and most effective natural gums and possesses unique properties that make it an excellent binder. It is composed of a complex mixture of glycoprotein and polysaccharides characterized by approximately 3% protein and 97% carbohydrates [17]. It has been used in different fields.…”
Section: Introductionmentioning
confidence: 99%